Rejection Of Judicial Review Petition By The Tax Court: A Legal Analysis Of The Legal Basis And Authority - Megeido, Alfrinno Archon; Sumaryoto, Otto; Patimah , Siti (Green Publisher Indonesia, 2025)
This article examines the legal basis and authority of the Tax Court in rejecting applications for judicial review (peninjauan kembali “PK”) in Indonesian tax dispute proceedings. Under Indonesia’s current tax court procedure, a PK is an extraordinary legal remedy filed to the Supreme Court through the Tax Court. The Tax Court’s role is not only to forward the case files to the Supreme Court but also to ensure that formal requirements are fulfilled. Applicable law (Law No. 14 of 2002 on Tax Court) limits PK applications to one filing and within a strict deadline. The Tax Court is empowered to refuse or return a PK application that does not meet these legal conditions – for example, if the application is a prohibited second PK, filed past the 3-month time limit, or missing required documents. This authority is grounded in statutory provisions, Supreme Court regulations, and the Tax Court’s own rules. Through normative juridical analysis, this article finds that the Tax Court’s refusal of non-compliant PK applications is legally justified as a gatekeeping function to uphold procedural law and ensure judicial efficiency. The conclusions highlight that the Tax Court’s limited authority in this context aligns with its duty to enforce formal requirements, while the substantive examination of tax disputes via PK remains the prerogative of the Supreme Court.